Study of the flux density variation along Saturn’s ring observed from National Observatory, Nagarkot, Nepal - Aryal, B; Nupane, HK; Shahi, SR (Scientific World, 2011)
We present a study of relative flux density along the Saturn’s ring. The image of the planet Saturn is taken from National Observatory located at Nagarkot, Nepal during January to March, 2010. Sixteen inch Schmidt-Cassegrain telescope is used to capture the image. The image is processed in the software ALADIN2.5. We have studied the flux density variation along Saturn’s ring from eastern to western region. The observed two-dimensional image of the ring of the planet Saturn is divided into five regions namely far-eastern, mid-eastern, middle, mid-western, far-western. We found that the total flux sometimes increases and sometimes decreases showing peak values at different regions along the ring. However, in the middle (across the planet), we found a fairly homogeneous emission. We took data of relative flux density in each pixel in these regions. The minimum and maximum values of flux density are found to lie in the range (5.9 – 12.7) x 10-7 MJy/str. The absorption feature is found to be prominent in western region. Key-words: Observation; Telescope; Saturn; Flux density. DOI: http://dx.doi.org/10.3126/sw.v9i9.5509 SW 2011; 9(9): 8-12